Diálogos interdisciplinares entre saúde e meio ambiente e a abordagem das questões ambientais na formação do enfermeiro no Brasil - Nunes, Camila Henriques (2019)
When considering nursing‘s relationship with broader society, it is a profession focused on promoting health, and as a consequence, environmental education. Thus, it is of critical importance that college nursing curriculums are aligned with the National Environmental Education Policy. With this in mind, the present study sought to identify gaps in different levels of nursing programs (undergraduate and graduate) with regards to environmental topics. It is quali-quantitative, descriptive, and exploratory research. The integration of environmental questions in graduate level nursing programs in Brazil was analyzed. Additionally, this study performed a case study of universities offering nursing college degrees in a medium-sized Brazilian city. Following a literature review, data were collected on political-pedagogic projects, curriculum matrices, course syllabi, as well as secondary data obtained from the Sucupira Platform. Empirical data were collected via questionnaires completed by undergraduate students in their last two semesters of a nursing program as well as through semi-structured interviews with program coordinators and other faculty members. Quantitative data were analyzed by the descriptive statistical Scott-Knott method. Qualitative data were examined by content analysis as proposed by Bardin. The results show the incipience of considering environmental questions in different levels of nursing programs. The predominant approach continues to anchor such issues in courses specifically about the environment to the detriment of interdisciplinarity. Regarding interdisciplinary environmental content, environmental issues appear mainly in direct comparison to questions about sociohistorical-cultural issues. The study suggests that the fragile environmental approach in nursing graduate programs in Brazil may be reflected in undergraduate education, and consequently, in the environmental awareness of nurses across the country.